Perbedaan Gejala pada Anak Autis yang Diet Bebas Gluten dan Kasein dengan yang Tidak Diet di Surabaya - Alifah Fajriyyatul Izzah; Widati Fatmaningrum; Roedi Irawan (Amerta Nutrition, 2020)
Background: Autism disorders can disrupt the quality of life of autism children. One popular diet therapy for children with autism is a gluten and casein free diet. Gluten and casein free diet based on opioid theory are still pros and cons.Objective: To determine the difference of symptoms in autistic children who are free from gluten and casein and those who are not.Method: An observational analytic cross-sectional study was conducted at several autistic therapy centers in Surabaya. The study was carried out in children with autism aged 3-12 years and was diagnosed by a specialist. The research subjects were selected by purposive sampling method. Data collected, including data on the child's identity, data on the identity of parents, data on gluten and casein implementation were obtained through the FFQ questionnaire and data on symptoms of autistic children were obtained from the ATEC questionnaire.Results: Autistic symptom scores were good for communication skills, social interactions, cognitive responses, and behavioral disorders in autistic children on diets rather than those who did not. Bivariate test results showed that there were significant differences in the variable behavior disorder (p=0.021) and the total score (p=0.018).Conclusion: There are differences in symptoms in autistic children who are free from gluten and casein and those who are not especially on behavioral disorders.ABSTRAKLatar Belakang: Gangguan autisme dapat mengganggu kualitas hidup anak autis. Salah satu terapi diet populer bagi anak autis adalah diet bebas gluten dan kasein. Diet bebas gluten dan kasein yang didasari oleh teori opioid masih menjadi pro kontra.Tujuan: Mengetahui perbedaan gejala pada anak autis yang diet bebas gluten dan kasein dengan yang tidak diet.Metode: Penelitian analitik observasional rancangan cross sectional dilakukan di beberapa pusat terapi autis di Surabaya. Penelitian dilakukan pada anak autis berusia 3 – 12 tahun dan telah didiagnosis oleh dokter ahli. Subyek penelitian dipilih dengan metode purposive sampling. Data yang dikumpulkan, meliputi data identitas anak, data identitas orang tua, data pelaksanaan diet bebas gluten dan kasein diperoleh melalui kuesioner FFQ serta data gejala pada anak autis diperoleh dari kuesioner ATEC.Hasil: Gambaran gejala pada anak autis yang diet bebas gluten dan kasein lebih ringan daripada yang tidak diet berupa gangguan kemampuan komunikasi, interaksi sosial, respon kognitif dan gangguan perilaku. Hasil uji bivariat menunjukkan ada perbedaan yang signifikan pada variabel gangguan perilaku (p=0,021) dan skor ATEC total (p=0,018).Kesimpulan: Ada perbedaan gejala pada anak autis yang diet bebas gluten dan kasein dengan yang tidak diet terutama pada gangguan perilaku.